Pensamentos algébrico e computacional no estudo do conceito de sequência: uma análise de coleções de livros didáticos de matemática - Perceval, Janaína Teixeira Leão (2025)
The development of algebraic and computational thinking is one of the objectives set by the National Common Curricular Base (BNCC) for the Mathematics curriculum, as both contribute to the formulation and solving of problems in various fields of knowledge. In this context, this research aims to identify how the collections of Mathematics textbooks for the Final Years of Elementary School, approved by PNLD/2024, address algebraic and computational thinking in their didactic-pedagogical orientations and in the proposed situations involving the concept of sequence and the representations mobilized. The theoretical framework is based on various studies and authors in Mathematics Education and Computing. Regarding the methodology, a qualitative research approach was chosen, utilizing assumptions from Content Analysis. The data source consists of nine collections of Mathematics textbooks for the Final Years of Elementary School, approved by PNLD/2024. After the pre-analysis, the research corpus was constituted by two types of messages: those from the didactic-pedagogical orientations and those from situations that address the concept of sequence. The exploration of the material allowed for the development, regarding the didactic-pedagogical orientations, of 103 Context Units, 33 Recording Units, four Thematic Axes, and two Categories of Analysis. As for the situations, 84 Context Units, corresponding to the number of selected situations, 33 Recording Units, six Thematic Axes, and two Categories of Analysis were identified. Upon analyzing the results and interpretations, it was found that the frequency of Recording Units emphasizing Algebraic Thinking in the textbook collections is low compared to Computational Thinking. Moreover, the understandings of these types of thinking are primarily based on what is outlined in the BNCC. The relationships between Algebraic and Computational Thinking are not explicit in most of the collections. However, some collections mention that Computational Thinking helps in understanding algebraic content, and vice versa. Regarding the situations proposed in the textbook collections, the need to diversify the nature of the elements that make up the sequences (geometric, numerical, and figurative), their development in terms of growth (increasing or decreasing), and what is expected from students at different educational levels (going beyond determining the next term, allowing for the mobilization of the three phases of a pattern) is emphasized, aiming at the development of Algebraic Thinking in connection with Computational Thinking.